Effect of introgressing dwarf gene from Bangladeshi indigenous to exotic breeds on egg production - Yeasmin, T.; Howlider, M.A.R.; Ahammad, M.U. (Science Alert, 2003)
An experiment was conducted to assess the effect of introgressing autosomal recessive dwarf gene (adw) from Bangladeshi indigenous (deshi) dwarf (DD) chicken to Rhode Island Red (RIR), White Leghorn (WLH) and Fayoumi (FO) on body weight and egg production. Deshi normal (DN), DD, RIR, WLH and FO were used in crossings to produce 8 genotypes; RIR, WLH, FO, DN, DD, RIR x DD, WLH x DD and FO x DD. At 19 weeks of age, for separation of crossbreds into normal and dwarf on the basis of shank length, altogether gave 11 genetic groups; RIR, WLH, FO, DN, DD, RIR x DD normal, WLH x DD normal, FO x DD normal, RIR x DD dwarf, WLH x DD dwarf and FO x DD dwarf. At 19 weeks of age, 154 pullets; 14 from each genetic group were individually caged up to 42 weeks of age to compare egg production performance. Introgression of adw gene significantly reduced mature body weight and feed intake and adw pullets utilized feed more efficiently into egg mass in comparison with their normal size counterparts. Conservation and improvement of deshi adw chicken is suggested for their future use in breeding for egg production.